Perkembangan Reformasi Birokrasi Organisasi Publik dan Partisipasi Publik - Niko Anindito (Lembaga Administrasi Negara, 2017)
Reform of government bureaucracy is urgent to implement when bureaucracy has been perceived as a system that causes the running of government and public services to run stagnant, long-winded, inefficient, too big and rigid organizations, corruption, and other bureaucratic issues. The low level of public confidence in the bureaucracy (or the high degree of mistrust) reflects the perception of low capability and integrity of the organization and state organizers in solving problems of public interest and vice versa. The public demand for quality public services requires the improvement of public management. The high level of complaints from service users indicatez that the government as a public organization is not yet fully able to create an acceptable service system in the eyes of the people. This has in part resulted in the decline of public confidence in public organizations. Keywords: bureaucratic reform, public organization, public trust